DNA methylation at cannabinoid type 1 and dopamine D2 receptor genes in saliva samples of psychotic subjects: Is there an effect of Cannabis use? - Martina Di Bartolomeo; Andrea Čerňanová; Veronika Petrušová; Serena Di Martino; Július Hodosy; Filippo Drago; Vincenzo Micale; Claudio D'Addario (Elsevier, 2024)
Psychosis is a characterizing feature of many mental disorders that dramatically affects human thoughts and perceptions, influencing the ability to distinguish between what is real and what is not. Both genetic and environmental factors, such as stressful events or drug use, play a pivotal role in the development of symptomatology and therefore changes in the epigenome may be of relevance in modeling a psychotic phenotype. According to the well-documented dysregulation of endocannabinoid and dopaminergic system genes in schizophrenia, we investigated DNA methylation cannabinoid type 1 receptor (CNR1) and dopamine D2 receptor (DRD2) genes in saliva samples from psychotic subjects using pyrosequencing. The epigenetic mark was significantly higher and directly correlated for both genes in psychotic subjects compared to healthy controls. We also showed that these DNA methylation levels were lower in psychotic subjects reporting current delta-9-tetrahydrocannabinol (THC) consumption, a well-known risk factor for developing psychosis throughout the lifespan, resembling those of controls at least for the DRD2 gene. Overall, our data confirm the key role of CNR1 and DRD2 gene regulation in psychosis and suggest DNA methylation levels at specific CpG sites as potential biomarkers, but just in those psychotic subjects not consuming THC.